Xây dựng và sử dụng tình huống giáo dục an toàn trong cuộc sống trong dạy học môn Tự nhiên và Xã hội ở tiểu học - Nguyễn Hồng Chiến, Nguyễn Hồng Chiến; Phan Thị Hồng, The; Nguyễn Thị, An; Đặng Huyền, Trang (Tạp chí Giáo dục, 2026)
Life safety education is an important component of the Natural and Social Sciences subject in primary school, contributing to students' ability to identify risks and develop skills to cope with unsafe situations in practice. This research aims to propose principles and procedures for constructing life safety education scenarios in the teaching of Natural and Social Sciences in primary school. The paper uses a theoretical research method combined with analysis of the curriculum, textbooks, and related materials to propose principles and procedures for constructing and using life safety education scenarios. The research results have identified the role of life safety education scenarios in teaching; proposed five principles for constructing scenarios, a three-step construction process, and a four-step usage process; and constructed several illustrative scenarios related to life safety education content in the Natural and Social Sciences subject in primary school. The research results contribute to supplementing the theoretical basis and providing a reference for teachers in designing and organizing lessons, thereby contributing to improving the effectiveness of safety education in line with the development of students' qualities and competencies.